Early life economic shocks and child health outcomes - Kazibwe, Douglas (2019)
This paper examines the relationship between commodity price shocks experienced in the early period of life and child health outcomes. The study uses a nationally representative household survey data from the Demographic and Health Surveys in Kenya matched with a time series of real producer prices of tea in estimating the effect of price shock on child health outcomes. The identification strategy of the paper relies on exogenous variations in the real producer price of tea and timing of child birth. The findings show that household income shocks induced by variations in tea prices are key drivers of child health outcomes. A one percentage increase in tea price in the early life stage improves child nutrition with a 32.67 standard deviation increase in height-for-age Z scores and reduces under-five mortality rate by 1.74 percentage points among children born in tea producing zones relative to those born in non-tea growing zones in Kenya.